The impact of competitive advantage on the investment timing in Stackelberg leader–follower game. Issue 3 (3rd July 2018) - Hoe, SingRu; Yan, Zhongfeng; Bensoussan, Alain
ABSTRACT: This short note clarifies how the Stackelberg leader's competitive advantage after the follower's entry affects the leader's optimal market entry decision and Stackelberg strategic interactions under uncertainty. Although the Stackelberg leader's first investment threshold remains constant and coincides with the monopolist's investment trigger, his second (third) investment threshold, which defines the exit (entry) of the first (second) investment interval, increases with an increased competitive advantage. With an increased competitive advantage, the probability of sequential investment equilibrium (simultaneous investment equilibrium) increases (decreases) irrespective of the level of volatility. Moreover, for a given level of competitive advantage, an increase in the volatility tends to decrease (increase) the probability of simultaneous investment equilibrium (sequential investment equilibrium). For a richer set of results, endogenous firm roles are examined and analyzed as well. The leader's preemptive threshold is negatively affected by his competitive advantage.